Pervaporation of methanol-methyl acetate binary mixtures - Sain, S; Dincer, S; Savascyi, OT (ELSEVIER SCIENCE SA, 1998)
In this study, the pervaporation behaviour of azeotrope forming methanol-methyl acetate binary mixtures of different compositions was investigated at 30 and 45 degrees C using cuprophane membranes. Experimental fluxes and selectivities of the permeating components were determined and evaluated on the basis of the feed mixtures and membranes. The effect of vacuum pressure on total flux and selectivity is discussed. (C) 1998 Elsevier Science S.A. All rights reserved.
Keywords: pervaporation; methanol; methyl acetate; Energy & Fuels; Engineering